Hybrid Delay-Phase Precoding in Wideband UM-MIMO Systems Under True Time Delay and Phase Shifter Hardware Limitations - Najjar, Akram; El-Absi, Mohammed; Kaiser, Thomas (IEEE transactions on wireless communications, 2024)
The exploitation of the substantial bandwidths available in the terahertz (THz) band has recently attracted considerable interest. However, beam squint effect is a significant obstacle in the design of wideband hybrid beamformers. The beam squint effect causes the radiation beam to deviate from the desired direction, resulting in substantial gain losses and hindering the effective utilization of available bandwidths. Delay-phase precoding (DPP), a combination of true time delay (TTD) elements and phase shifters (PSs) in the analog domain, has emerged as a potential solution to overcome the beam squint effect and maintain practical system design. However, existing hybrid precoding schemes that assume infinite resolution and unbounded range TTDs, as well as infinite resolution PSs, impose a significant burden in terms of hardware complexity and power consumption. In this paper, we introduce the Delta-Delay-Phase Precoding (DDPP) architecture, which significantly reduces the required delay range of TTDs, outperforming existing state-of-the-art solutions in the literature. Importantly, the proposed architecture maintains consistently superior performance, even as the number of antenna elements increases, making it scalable for UM-MIMO systems. Additionally, we propose hardware-aware designs for the hybrid analog precoder to combat beam squint effect while complying with the hardware limitations of TTDs and PSs. We formulate the design of TTDs and PSs as a joint optimization problem subject to their finite-resolution constraints. To tackle this non-convex optimization problem, we propose an iterative precoding algorithm based on alternating minimization. Simulation results demonstrate the superiority of the proposed hybrid analog precoding schemes over recent literature works. Particularly, the proposed precoding schemes achieve near-optimal performance despite the hardware limitations of TTDs and PSs.